The Tight Esophagus - Bougies or Balloons - John S Goff (Canadian Journal of Gastroenterology)
Esophageal strictures can be managed with a variety of techniques. Each device for dilation has its advantages and disadvantages which are important in selecting the appropriate one for each situation. Stricture management with dilation may require many sessions over a prolonged time. Complications of dilation are infrequent, but perforation must be watched for closely since its consequences are so serious. The most important factor in stricture management with dilators is physician familiarity with the method selected.